2018
DOI: 10.15666/aeer/1603_31453157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recovery From Acute Lung Injury Induced by Intratracheal Instillation of Zinc Oxide Nanoparticles

Abstract: Abstract. Zinc oxide nanoparticles (ZnO-NPs) can potentially cause adverse health effects because they are highly soluble and widely used. We evaluated the effect of ZnO-NPs in rat lung. ZnO-NPs were administered via intratracheal instillation to Sprague Dawley rats at three different dosages (1, 5, and 10 mg/kg body weight). Macrophage numbers, total cell count, and total protein concentrations in bronchoalveolar lavage fluid (BALF) highly increased at day 1 in a dose-dependent manner relative to those in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Signs included evidence of phagocytosis by macrophage, lymphocytic perivasculitis and pribronchiolitis and interstitial inflammation [7]. The findings of previous studies suggested that other routes of exposure to ZnO-NPs as intratracheal instillation could lead also to severe tissue damage and could progress to chronicpathological conditions [14,15]. The oxidative stress is a known contributor to…”
Section: Immunohistochemical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signs included evidence of phagocytosis by macrophage, lymphocytic perivasculitis and pribronchiolitis and interstitial inflammation [7]. The findings of previous studies suggested that other routes of exposure to ZnO-NPs as intratracheal instillation could lead also to severe tissue damage and could progress to chronicpathological conditions [14,15]. The oxidative stress is a known contributor to…”
Section: Immunohistochemical Resultsmentioning
confidence: 99%
“…The lungs are particularly susceptible to ZnO-NPs because of its high vascularity and ability to concentrate toxins [11,12]. Up to our knowledge, the vast majority of the previous studies on lung toxicity of ZnO-NPs were addressing the short term exposure to it, and mostly the exposure was through inhalation and intratracheal instillation [13][14][15]. The toxic effect of short duration exposure to orally ingested ZnO-NPs on lungs was assessed in previous studies [10,12].…”
mentioning
confidence: 99%
“…The intra-tracheal instillation of ZnONP in mice induced acute lung inflammation and lung injury with a significant increase in the LDH level detected in bronchial alveolar lavage fluids (BALF) [157,158]. Moreover, ZnONP induced the recruitment of macrophages and neutrophils with high levels of proinflammatory cytokines, such as IL-6 in BALF, after pulmonary exposure in mice [159][160][161]. Furthermore, ZnONP appears to have an adjuvant-like response to allergen ovalbumin (OVA) and induce Th2 responses in mice [154].…”
Section: In Vivo Znonp Toxicitymentioning
confidence: 99%